The Role of Cell Adhesion and Cytoskeleton Dynamics in the Pathogenesis of the Ehlers-Danlos Syndromes and Hypermobility Spectrum Disorders - Malek, Sabeeha; Köster, Darius V. (Frontiers in Cell and Developmental Biology, 2021)
The Ehlers-Danlos Syndromes (EDS) are a group of 13 disorders, clinically defined through features of joint hypermobility, skin hyperextensibility, and tissue fragility. Most subtypes are caused by mutations in genes affecting the structure or processing of the extracellular matrix (ECM) protein collagen. The Hypermobility Spectrum Disorders (HSDs) are clinically indistinguishable disorders, but are believed considered to lack a genetic basis. The pathogenesis of all these disorders however, remains poorly understood. Genotype-phenotype correlations are limited, and findings of aberrant collagen fibrils are inconsistent and associate poorly with the subtype and severity of the disorder. The defective ECM however, also has consequences on cellular processes. EDS/HSD fibroblasts exhibit a dysfunctional phenotype including impairments in cell adhesion and cytoskeleton organization, though the pathological significance of this has remaineds unclear. Recent advances in our understanding of fibroblast mechanobiology however, suggests these changes may actually actually reflect features of a pPathomechanism we herein define. This review therefore, departs from the traditional view where of EDS/HSD, where pathogenesis is mediated by the structurally defective ECM. , and we present here, the evidence that demonstrates otherwise. WeInstead, we propose that EDS/HSD may be a disorder of membrane-bound collagen, and consider how aberrations in cell adhesion and cytoskeletonal dynamics could drive the abnormal properties of the connective tissue, and may even be responsible for the pathogenesis of EDS/HSD.